Social cultural factors influencing health seeking practices among men suffering from lower urinary tract symptoms attending surgical outpatient clinic at a county referral hospital in Kenya - Mwendia Muriuki, Festus; Wambua Mbithi, Bernard; Oluchina, Sherry (International Journal of Advanced Nursing Studies, 2020)
Health seeking practices is critical towards early screening, detection and control of Lower Urinary Tract Symptoms (LUTS) whereby human prostate gland is the major cause of benign prostate hyperplasia (BPH) and prostate cancer (PCA), which mostly accounts for LUTS. Social cultural factors such as cultural beliefs, educational level, income level and religion among many others have a direct influence on health seeking practices both positively and negatively in as far as LUTS are concerned. The researcher explored social cultural factors influencing health seeking practices among men with LUTS attending surgical outpatient clinic at Meru level five hospital (Kenya). De-scriptive cross-sectional study design was used to collect data from 120 men with LUTS, and 4 health workers. Census method was used to select the study participants with questionnaires, interview guide and focused group discussion used as instruments of data collection. Quantitative data was analyzed using Statistical Package for Social Sciences (SPSS) software version 22, whereas the qualitative data was analyzed using qualitative techniques. Descriptive statistics were computed to generate percentages and frequencies, which were then presented in tables and charts. Logistic regression was used whereby P-values were employed to determine the statistical significance of results with cut off set at (p â‰¤0.05). Majority (67.0%) of the patients with LUTS were aged between 61-70 years. Also, majority (68.8%) of the respondents had primary level of education, with majority (72.0%) of them being farmers with an income level of below Ksh. 20,000. The study results showed that social cultural factors had statistical significant influence on health seeking practices among men with LUTS.Â Â Â Â